Ảnh hưởng của cấu trúc hình học đến đặc trưng volt-ampe của các vi điện cực vàng tự chế tạo. - Mai, Phan Thị Ngọc; Hà, Mai Thị Thu (Vietnam Journal of Chemistry, 2012)
This article presents the recent developments of microelectrodes both in single and array configurations. The effects of gold microdisk electrode arrangements in array on cyclic voltametry response were investigated. Array electrode in studied cases produce scan rate independent voltammograms with steady-state characteristics. It was shown that the voltametric responses of array microelectrode were simply the total response of all individual microelectrode. It is in agreement with other published papers.